Student-Teacher Relationship in Online Class of Nepali Schools during COVID-19 - Khadka, Jiban (Nepal Journal of Multidisciplinary Research, 2020)
In traditional or online class, student-teacher relationship plays critical role in the overall growth of the students. Following the internet-based survey of 401 students from 18 public and private schools across the country, this study explored the online class status of the students, and their academic and social relations with their teachers during COVID-19 pandemic. The literature-based questionnaire was split into two parts (student backgrounds and online class status, and relationship) and had the Cronbach's alpha .892 for the relation related items. The results of descriptive and inferential statistics indicate that the students had a high degree of academic and social relation. It is significantly difference across gender (for social relation), age, class level, school type and internet connectivity for both academic and social relations but it was insignificant across students' residing regions, caste, parents' education and the e-devices used in the online class. Based on the findings, this study advances some ways to increase active involvement of female students through inclusive participation of parents, schools and society, and to break through by supporting effective pedagogical practices and building warmth and positive online classes in establishing relation with secondary, adolescents or private school students.